Analisis Profitabiltas Bank Yang Terdaftar Di Bursa Efek Indonesia (BEI) Sebelum Dan Saat Pandemi Covid-19 - Sahetapy, William Yonathan; Suparwati, Yohana Kus (Magister Manajemen STIE Bank BPD Jateng, 2024)
This research aims to determine differences in the profitability ratios of banks listed on the IDX before the pandemic and during the Covid-19 pandemic. The sample in this study is the financial statements of banks listed on the IDX for 2018-2021. The research method used is descriptive quantitative method with purposive sampling data collection technique. The hypothesis in this study is whether there is a difference in the profitability ratios of banks listed on the IDX before and during the Covid-19 pandemic. The data will be analyzed using SPSS Version 25, and the test performed is the Non-Parametric Difference test with the Wilcoxon test. Based on the research results obtained, there were significant differences in the profitability ratios of banks listed on the IDX before and during the Covid-19 pandemic